Electronic monitoring devices during substance use treatment are associated with increased arrests among women in specialty courts. (2nd September 2020) - Reingle Gonzalez, Jennifer; Johansson-Love, Jill; Edmonds, Laura; Jetelina, Katelyn
ABSTRACT: Background : Electronic monitors (EMs) are commonly used as a sanction and to improve compliance with substance use treatment and reduce re-arrest in criminal justice settings. However, there is minimal evidence for their effectiveness, especially among women. Objectives : We examined whether the use of EMs (i.e., devices placed on one's body to encourage treatment compliance) increased rates of substance use treatment completion, and as a result, reduced re-arrest and substance use among women offenders. Methods : We sampled 114 women referred to residential substance use treatment and a subsample of 102 women charged with felonies. Logistic regression models accounting for clustering of time within person were fit. Results : Overall, EMs were associated with 3.13 greater odds of re-arrest after accounting for criminogenic risk indicators; however, no association was detected among women charged with felonies only. Women who were assigned to EMs were significantly less likely to report illicit drug use in the past 30 days, and women charged with felonies were less likely to report both alcohol and illicit drug use in the past 30 days. There was no association between EM assignment and treatment completion or positive urinalysis result. Conclusion : EM provision did not enhance the retention of women in residential treatment and the presence of an EM was associated with a more than tripling in the odds of re-arrest. Results also suggest that EM use for women in Specialty Courts may have some limited utility in reducing substance use; however, the mechanism driving this effect remains unclear.